Marfany, Roberto H.: "Visperas de Mayo". Buenos Aires, Theoría, 1960, 107 págs. - Molinari de Acevedo, Alba (Universidad Nacional de Cuyo. Facultad de Filosofía y Letras. Instituto de Historia., 1961)

(untitled)
Fil: Molinari de Acevedo, Alba.